A comparison of two maintenance strategies: Reliability-centred maintenance and total productive maintenance - I. B. Hipkin (South African Journal of Business Management, 1993)
Improvements in the manufacturing sector have been attained through the use of a variety of management interventions. These have all concentrated on materials management and the production process. One functional area that has been neglected is the maintenance of physical assets. In this article two maintenance management approaches are compared from a philosophical and strategic point of view: reliability-centred maintenance (RCM) and total productive maintenance (TPM). The two are conceptually different, although there are common elements. Reliability-centred maintenance provides a structured methodology and concentrates on technical Issues such as failure consequences and the technical feasibility and effectiveness of maintenance, with some emphasis on the human factors. Total productive maintenance seeks to maximize equipment effectiveness by the complete elimination of failures and relies on the work of autonomous groups. Much emphasis is placed on the human component From a strategic point of view, both approaches require organizational changes which may result in a dilution of managerial power.
Keywords: 650